Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the equation [tex]\(\sqrt{3x + 16} = x + 2\)[/tex], let's go through the steps methodically.
1. Square both sides to eliminate the square root:
[tex]\[ (\sqrt{3x + 16})^2 = (x + 2)^2 \][/tex]
This gives:
[tex]\[ 3x + 16 = x^2 + 4x + 4 \][/tex]
2. Rearrange the equation to set it to zero:
[tex]\[ x^2 + 4x + 4 - 3x - 16 = 0 \][/tex]
Simplify the terms:
[tex]\[ x^2 + x - 12 = 0 \][/tex]
3. Factor the quadratic equation:
[tex]\[ x^2 + x - 12 = (x - 3)(x + 4) = 0 \][/tex]
4. Find the roots:
[tex]\[ x - 3 = 0 \quad \text{or} \quad x + 4 = 0 \][/tex]
Thus,
[tex]\[ x = 3 \quad \text{or} \quad x = -4 \][/tex]
5. Verify the roots by substituting them back into the original equation to check for extraneous solutions:
- For [tex]\(x = 3\)[/tex]:
[tex]\[ \sqrt{3(3) + 16} = 3 + 2 \][/tex]
[tex]\[ \sqrt{9 + 16} = 5 \][/tex]
[tex]\[ \sqrt{25} = 5 \][/tex]
This is true, so [tex]\(x = 3\)[/tex] is a valid solution.
- For [tex]\(x = -4\)[/tex]:
[tex]\[ \sqrt{3(-4) + 16} = -4 + 2 \][/tex]
[tex]\[ \sqrt{-12 + 16} = -2 \][/tex]
[tex]\[ \sqrt{4} = -2 \][/tex]
Since [tex]\(\sqrt{4} = 2\)[/tex] and not [tex]\(-2\)[/tex], [tex]\(x = -4\)[/tex] is not a valid solution.
After checking, we find that the only valid solution is:
[tex]\[ \{3\} \][/tex]
Therefore, the correct answer is:
3) [tex]\(\{3\}\)[/tex]
1. Square both sides to eliminate the square root:
[tex]\[ (\sqrt{3x + 16})^2 = (x + 2)^2 \][/tex]
This gives:
[tex]\[ 3x + 16 = x^2 + 4x + 4 \][/tex]
2. Rearrange the equation to set it to zero:
[tex]\[ x^2 + 4x + 4 - 3x - 16 = 0 \][/tex]
Simplify the terms:
[tex]\[ x^2 + x - 12 = 0 \][/tex]
3. Factor the quadratic equation:
[tex]\[ x^2 + x - 12 = (x - 3)(x + 4) = 0 \][/tex]
4. Find the roots:
[tex]\[ x - 3 = 0 \quad \text{or} \quad x + 4 = 0 \][/tex]
Thus,
[tex]\[ x = 3 \quad \text{or} \quad x = -4 \][/tex]
5. Verify the roots by substituting them back into the original equation to check for extraneous solutions:
- For [tex]\(x = 3\)[/tex]:
[tex]\[ \sqrt{3(3) + 16} = 3 + 2 \][/tex]
[tex]\[ \sqrt{9 + 16} = 5 \][/tex]
[tex]\[ \sqrt{25} = 5 \][/tex]
This is true, so [tex]\(x = 3\)[/tex] is a valid solution.
- For [tex]\(x = -4\)[/tex]:
[tex]\[ \sqrt{3(-4) + 16} = -4 + 2 \][/tex]
[tex]\[ \sqrt{-12 + 16} = -2 \][/tex]
[tex]\[ \sqrt{4} = -2 \][/tex]
Since [tex]\(\sqrt{4} = 2\)[/tex] and not [tex]\(-2\)[/tex], [tex]\(x = -4\)[/tex] is not a valid solution.
After checking, we find that the only valid solution is:
[tex]\[ \{3\} \][/tex]
Therefore, the correct answer is:
3) [tex]\(\{3\}\)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.